KAJIAN LITERATUR PENDEKATAN KEPEMIMPINAN MANAJEMEN BERBASIS SEKOLAH DI SMK DALAM MENINGKATKAN KESIAPAN KERJA SISWA - Hatta, Mega Amelia Prihatini; Giatman, M.; Ernawati, Ernawati (Ensiklopedia of Journal, 2024)
Abstract: Vocational High Schools (SMK) are crucial in preparing graduates who are ready to work but still face challenges related to optimal leadership roles. This study discusses the role of leadership in SMK in preparing a generation ready to work through the implementation of school-based management. This research focuses on understanding how school principals can play an essential role in creating a learning environment supporting employability skills development. This study used A literature review as the primary method, and various sources related to school-based educational leadership and management were reviewed. The study results show that effective leadership can increase teacher cooperation, prepare a curriculum based on industry needs, and strengthen a productive school culture. The implication of this study is the need to increase school leadership capacity to strengthen students' work readiness.Keywords: Leadership, Vocational School, School-Based Management, Job Readiness.